Interactive collaborative robotics : third international conference, ICR 2018, Leipzig, Germany, September 18-22, 2018, Proceedings /: third international conference, ICR 2018, Leipzig, Germany, September 18-22, 2018, Proceedings. (2018) - Unknown
No abstract available